SURE – EU Capacity for Stabilising Employment and Incomes in the Pandemic - László Andor (Intereconomics, 2020)
On 2 April 2020, the European Commission (2020) duly put forward a proposal for the creation of a European instrument for temporary Support to mitigate Unemployment Risks in an Emergency (SURE). This bold and innovative move must be welcome, but the actual profile of this new instrument requires clarification to avoid misunderstandings, false expectations and eventual disappointment.
Keywords: 330